Relationship of left ventricular size to left atrial and left atrial appendage size in sinus rhythm patients with dilated cardiomyopathy - Bakalli, A; Georgievska-Ismail Lj; Musliu, N; Kocinaj, D; Gashi, Z; Zeqiri, N (Academy of Medical Sciences of Bosnia and Herzegovina, 2012)
Introduction: Thromboembolic events are a frequent cause of mortality in patients with congestive heart failure. The aim of or study was to evaluate the relationship of left ventricular end diastolic diameter (LVEDD) to left atrial (LA) size and left atrial appendage (LAA) size in patients with dilated cardiomyopathy in sinus rhythm, as well as to determine the prevalence of thrombi in LV and LA /LAA. Methods: This was a prospective cross-sectional study, conducted from December 2009 until December 2011. The study included 95 patients with dilated cardiomyopathy in sinus rhythm. Patients with swallowing problems, acute myocardial infarction, atrial fibrillation/flatter, severe systolic dysfunction, and/or patients who were taking oral anticoagulation therapy were excluded. Results: Mean patient age was 58.6 ± 12.2 years and 68.4% were men. Mean LVEDD of our population was 66.5 ± 6.5 mm, while mean LA atrium, LA volume and LAA maximal area were 46 ± 5.1 mm, 87.2 ± 38.7 cm3 and 4.7 ± 1.2 cm2, respectively. LA diameter (p<0.001) and LAA maximal area (p=0.01) showed to be independent predictors of LV size. LV thrombus was detected in 13 (13.7%) patients, while LAA thrombus in 46 (48.4%) patients of our study population. Conclusions: In conclusion, dilated LV size is associated with enlarged LA and LAA size. On the other hand, dilation of LV, LA and LAA is related to high prevalence of left chamber cardiac thrombi.
Keywords: thrombus; dilated cardiomyiopathy; left atrial appendage area